Analiza kartografske projekcije karte Nova Lusitania - Santos, Kairo da Silva; Lapaine, Miljenko; Santos, José Gomes dos; Fernandes, Manoel do Couto; Corrêa Martins, Francisco José; Laeta, Tainá; de Menezes, Paulo Márcio Leal (Kartografija i geoinformacije, 2021)
The map named Carta Geographica de Projecçaõ Espherica Orthogonal da Nova Lusitania ou America Portugueza e Estado do Brazil from 1798, together with its 1795 (?), 1797 and 1803 versions, is undoubtedly one of the cartographic monuments developed by Portuguese cartography from the late eighteenth century. Its organizer was the geographer, astronomer, and frigate captain Antonio Pires da Silva Pontes Leme, who relied on the work of 34 people, including astronomers, geographers, and engineers, who, although only mentioned in the 1798 version, contributed to the creation of all versions. All of them are similar in appearance, but differ in size, content, details, amount, and distribution of toponyms, which will be the subject of another paper. The greatest similarity, however, concerns the defined map projection. The objective of this paper is to analyse and present the possible hypotheses and conclusions about which map projection was adopted for all versions of Nova Lusitania , through the identification of characteristics that allowed to infer and prove the adopted projection. The applied methodology verified that in the bibliographic search, the information about the map structure is insufficient. An article presented by General Djalma Polli Coelho in October 1950 states that the projection suggested by its title, as orthogonal spherical, appeared to be the Sanson-Flamsteed equal-area projection. However, the expression Carta Geographica de Projecçaõ Espherica Orthogonal allows us to infer also the transverse orthographic projection. Through parameters defined for the two projections, it was possible to establish the comparative elements for a cartographic analysis, which would allow us to conclude and prove the structure adopted for the map, allowing to conclude if the adopted projection for the Nova Lusitania was an azimuthal orthographic equatorial projection, or a Sanson-Flamsteed, sinusoidal projection on the meridian 315°, defined west-east, (counterclockwise), from the El Hierro (Ferro) Island. This meridian is referenced approx. –62°39'46" off the Greenwich meridian. Carta Geographica de Projecçaõ Espherica Orthogonal da Nova Lusitania ou America Portugueza e Estado do Brazil iz 1798. godine, zajedno sa svojim inačicama iz 1795. (?), 1797. i 1803. godine, nesumnjivo je jedan od kartografskih spomenika izrađenih u Portugalu krajem osamnaestog stoljeća. Njezin je organizator bio geograf, astronom i kapetan fregate Antonio Pires da Silva Pontes Leme koji se oslanjao na rad 34 osobe, uključujući astronome, geografe i inženjere, koji su, iako samo spomenuti u inačici iz 1798. godine, pridonijeli izradi svih drugih. Sve su inačice izgledom slične, ali se razlikuju po veličini, sadržaju, detaljima, količini i distribuciji toponima, no to će biti predmet drugoga rada. Međutim, najveća se sličnost odnosi na kartografsku projekciju. Cilj je ovoga rada analizirati i prikazati moguće hipoteze i zaključke o tome koja je kartografska projekcija usvojena za sve inačice Nove Luzitanije identificiranjem karakteristika koje su omogućile zaključivanje i dokazivanje usvojene projekcije. Primijenjena je metodologija potvrdila da su u bibliografskom pretraživanju podatci o strukturi karte nedovoljni. U članku koji je u listopadu 1950. predstavio general Djalma Polli Coelho navodi se da se čini da je projekcija predložena naslovom kao ortogonalna sferna projekcija zapravo ekvivalentna Sanson-Flamsteedova projekcija. Međutim, naslov Carta Geographica de Projecçaõ Espherica Orthogonal omogućuje nam zaključak da je to možda poprečna ortografska projekcija sfere. S pomoću parametara koji definiraju dvije projekcije bit će moguće uspostaviti usporedne elemente za kartografsku analizu, što bi nam omogućilo da zaključimo i dokažemo strukturu usvojenu za kartu Nova Lusitanija – je li ona poprečna ortografska projekcija ili Sanson-Flamsteedova sinusna projekcija sa srednjim meridijanom od 315°, definiranim u smjeru zapad-stok (u smjeru suprotnom od kazaljke na satu) s otoka El Hierro (Ferro). Taj je meridijan smješten približno –62°39ʹ46ʺ u odnosu na grinički meridijan.